THE HISTORICITY AND THE TRADITION OF PESANTREN BENDA KEREP - Kairin Toha (IAIN Syekh Nurjati Cirebon, 2017)
AbstractIn fifteenth century Islam had strived in Java. Mainly in West Java, the islamic courts – Kraton-kraton – of Cirebon had played an enermous role at this early development of Islam. Furthermore, the second former ruler of Kraton Ciebon, Syekh Syarif Hidayatullah or well known as Sunan Gunung Djati, was one of Wali Songo (the nine sints) in Java, whose descents then spreaded to the rural village around the court to build pesantrens. Therfore, between the 19th and 20th centuries, Cirebon was one of the centres of pesantren in Java by the establishment of some pesantrens. Pesantren Benda Kerep is, instead of Pesantren Buntet, Gedongan, and Kempek, one of the inheritances of the islamic court, Kraton Cirebon. Unlike other traditional pesantrens in Cirebon, It has kept its tradition, so that it now becomes the fossil of ancient civilisation of Cirebonese. However, it should eventually receive some ways of alternation.Keywords: Tradition, Pesantren, and alternation